Pancreatic acinar cells - A normal finding at the gastroesophageal junction? Data from a prospective Central European multicenter study - Schneider, Nora I.; Plieschnegger, Wolfgang; Geppert, Michael; Wigginghaus, Bernd; Höss, Gabriele M.; Eherer, Andreas; Wolf, Eva Maria; Rehak, Peter; Vieth, Michael; Langner, Cord (Virchows Archiv, 2013)
Pancreatic acinar cells are a well-recognized finding at the gastroesophageal junction, but their histogenesis and biological significance are unclear. From the prospective Central European multicenter histoGERD trial, we recruited 1,071 individuals undergoing gastroscopy for various non-selected reasons. Biopsy material was systematically sampled from the gastroesophageal junction and from the stomach. The study aimed to assess the prevalence of pancreatic acinar cells and to relate their presence to various histologic and clinical features. Overall, pancreatic acinar cells were observed in 184 (17.2 %) participants. Individuals diagnosed with pancreatic acinar cells were slightly younger than those without (median 50 vs. 53 years; p = 0.009). There was no association with patients' symptoms and/or complaints or with an endoscopic diagnosis of esophagitis or Barrett's esophagus. Regarding histology, pancreatic acinar cells were not associated with features of the squamous epithelium indicating reflux disease, such as basal cell hyperplasia, papillary elongation, dilation of intercellular spaces, and inflammatory cell number, but were associated with the presence of cardiac mucosa (p < 0.001), oxyntocardiac mucosa (p < 0.001), and intestinal metaplasia (p = 0.038), respectively. No association with Helicobacter pylori infection or diagnosis of gastritis was noted. In conclusion, pancreatic acinar cells are a common finding at the gastroesophageal junction, and no association with either reflux disease (histologically or endoscopically) or diagnosis of gastritis was observed. These data suggest a congenital rather than an acquired (metaplastic) origin of pancreatic acinar cells at the gastroesophageal junction. This questions the term "pancreatic acinar metaplasia" which is currently widely used for their diagnosis. © 2013 Springer-Verlag Berlin Heidelberg.
CRIS-Team Scopus Importer:2025-03-05
Keywords: Gastric cardia; Gastritis; Pancreatic acinar metaplasia; Prevalence; Reflux disease